2020
DOI: 10.1016/j.ygyno.2019.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow-up of quality of life for participants undergoing risk-reducing salpingo-oophorectomy or ovarian cancer screening in GOG-0199: An NRG Oncology/GOG study

Abstract: h i g h l i g h t s Ovarian cancer screening did not adversely impact health-related Quality of Life. Health-related QOL improved during follow-up for participants selecting RRSO. Ovarian cancer-related stress improved after RRSO. No adverse effects of RRSO or OCS on psychological and emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Eight studies 34,35,51,[71][72][73][74][75] reported HRQoL including physical and mental components was unaffected after RRSO. Mai 76 and Johansen 50 reported improved HRQoL post-RRSO, and J o u r n a l P r e -p r o o f stable HRQoL with screening for women with increased OC-risk. Five studies 52,77-80 reported short-term deficits (poorer physical/social functioning, more physical role limitations, greater pain/discomfort, less vitality) following RRSO; Fang 77 reported that despite short-term deficits in most components (1-month, SF-36), most women recovered to baseline functioning at 6 and 12-months follow-up.…”
Section: Qol Outcomes After Rrso -Hrqolmentioning
confidence: 98%
See 1 more Smart Citation
“…Eight studies 34,35,51,[71][72][73][74][75] reported HRQoL including physical and mental components was unaffected after RRSO. Mai 76 and Johansen 50 reported improved HRQoL post-RRSO, and J o u r n a l P r e -p r o o f stable HRQoL with screening for women with increased OC-risk. Five studies 52,77-80 reported short-term deficits (poorer physical/social functioning, more physical role limitations, greater pain/discomfort, less vitality) following RRSO; Fang 77 reported that despite short-term deficits in most components (1-month, SF-36), most women recovered to baseline functioning at 6 and 12-months follow-up.…”
Section: Qol Outcomes After Rrso -Hrqolmentioning
confidence: 98%
“…-Sexual function Decreased sexual pleasure, more sexual discomfort, and less frequent sex were reported after RRSO in 13 studies. 34,35,[50][51][52]70,72,74,[76][77][78]81,82 This included both pre-menopausal and postmenopausal women. Four studies 50,52,81,82 showed that HRT may mitigate these risks for premenopausal women but not to pre-surgical levels.…”
Section: Qol Outcomes After Rrso -Hrqolmentioning
confidence: 99%
“…Each individual's decision making and timing for these preventive measures are complex and often highly influenced by anxiety about developing a lethal disease. Women with high-risk genetic mutations who undergo BSO report less cancer-specific worry and distress compared with those who opt for close gynecologic screening as a preventive measure (Madalinska et al, 2005;Mai et al, 2020), but outcomes for depression and anxiety in general are similar between groups (Mai et al, 2020). Younger and nulliparous women may benefit from psychological intervention to manage uncertainty and cope with cancer-related worry.…”
Section: Depressed Mood and Anxietymentioning
confidence: 99%
“…However, risk-reducing BSO, especially in premenopausal women, is associated with reduced pleasure and greater discomfort with sexual activity compared to presurgical levels (Hall et al, 2019). In women at high risk for ovarian cancer, those who opt for risk-reducing BSO report poorer sexual function after 1 year compared with those who opt for screening only (Mai et al, 2020). Vaginal dryness and vulvovaginal atrophy resulting from the loss of ovarian estrogens lead to discomfort during sexual activity and are prevalent in both surgically and naturally menopausal women.…”
Section: Sexual Functionmentioning
confidence: 99%
“…Women undergoing prophylactic oophorectomy while in their 40s are at higher risk for osteopenia and osteoporosis. 47 , 48 Post-oophorectomy bone mineral density (BMD) measurements were assessed in a retrospective cohort of 95 women who had prophylactic oophorectomy at a mean age of 48 years. A significant annual decrease in BMD from baseline was noted among both pre- and postmenopausal women at time of surgery.…”
Section: Survivorship Issuesmentioning
confidence: 99%